Study and Characterization of Polyvinyl Alcohol-Based Formulations for 3D Printlets Obtained via Fused Deposition Modeling - Sofiya Ilieva; Dilyana Georgieva; Valentina Petkova; Milen Dimitrov (MDPI AG, 2023)
Three-dimensional (3D) printing has emerged as a new promising technique for the production of personalized dosage forms and medical devices. Polyvinyl alcohol is prominently used as a source material to produce 3D-printed medicines via fused deposition modeling (FDM)-a technology that combines hot melt extrusion and 3D printing. A preliminary screening of three grades of PVA indicated that partially hydrolyzed PVA with a molecular weight (MW) of 31,000-50,000 and plasticized with sorbitol was most suitable for 3D printing. Paracetamol was used as a model drug. The materials and the produced filaments were characterized by X-ray powder diffraction (XRPD), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). The complex viscosity (η*) of the polymer melts was determined as a function of the angular frequency (ω) at the printing temperature to assess their printability. Three-dimensional printlets with a 40% infill exhibited an immediate release of the API, while tablets with a higher infill were prone to a prolonged release regardless of the filament drug loading. A factorial design was used to give more insight into the influence of the drug-loading of the filaments and the tablet infill as independent variables on the production of 3D printlets. The Pareto chart confirmed that the infill had a statistically significant effect on the dissolution rate after 45 min, which was chosen as the response variable.